North American Survey on HPV and p16 Testing in Head and Neck Cancer. (23rd August 2013) - Maniakas, Anastasios; Moubayed, Sami Pierre; Ayad, Tareck; Guertin, Louis; Nguyen‐Tan, Phuc‐Felix; Gologan, Olga E.; Christopoulos, Apostolos
Abstract : Objectives: 1) Evaluate systematic testing of human papillomavirus (HPV) and p16 status on head and neck cancer in North America. 2) Assess if HPV or p16 status is used to influence treatment in this population. Methods: An online survey was sent to three professional associations: the American Head & Neck Society, the Canadian Society of Otolaryngology, and the Quebec Association of Otolaryngology. Inclusion criteria were physicians practicing in North America. Incomplete surveys were disregarded. Chi‐square analyses were conducted. Results: There was a response rate of 20% with a total of 216 complete responses. Most respondents were otolaryngologists (196; 90.7%), English‐speaking (178; 82.4%), and practicing in an academic setting (138; 63.9%). Routine HPV or p16 testing was performed by 146 respondents for the oropharynx, 69 for oral cavity, and 44 for other subsites. Most physicians (113; 77.4%) test for both HPV and p16, while 58.3% indicated that HPV/p16 status influences their treatment approach for oropharyngeal cancer. In Quebec, 15.4% of respondents test for HPV/p16, versus 61.0% in the rest of Canada and 88.1% of the American Head & Neck Society members ( P < 0.001). Practicing in an academic center of having a primarily (≥50%) oncology practice was associated with a higher rate of HPV/p16 testing (P < 0.001). Conclusions: The majority of North American otolaryngologists test for HPV or p16 status in head and neck cancer. Furthermore, the majority indicate that this testing influences their treatment approach for oropharyngeal cancer. Concurrently, multiple treatment deintensification protocols for this type of cancer are currently underway.